ANALYSIS OF THE QUESTIONNAIRE OF COACHES IN THE TRAINING OF ATHLETES-HIGH JUMPERS (Scientific journal of the Fergana State University, 2024)
This study explores optimal training and selection practices for high jump athletes. A survey of coaches reveals preferences for starting athlete selection predominantly at ages 8-9 and favors a training balance skewed towards more specialized physical training (70% MJT) for novices. Selection criteria among coaches vary, with a majority prioritizing anthropometric and physical attributes, while also considering genetics and personal interest.